Análise da prevalência de fatores de risco cardiovascular em adolescentes do município de Veranópolis, RS - Pitrez Filho, Manoel Luiz Soares (2000)
Objective: To describe the prevalence of coronary artery disease (CAD) risk factors in adolescents. Methods: We investigated 214 subjects from 10 to 18 years of age, (105 males and 109 females). Sex, total cholesterol, LDL-cholesterol, HDL-cholesterol, triglyceride, glucose, body mass index (BMI), systolic blood pressure, diastolic blood pressure, and family history of CAD (parents with cardiovascular events before 55 years old and other family members, were analysed in these patients. Results: Total holesterol, HDL-c and triglyceride levels werw significantly higher in females than in males. However, all values were in between normal range levels. The hipercholesterolemia, elevated blood pressure, hiperglicemia, overweight, and CAD familial history were respectively: 12%, 43%, 3%, 53% e 61% in male adolescents and 22%, 53%, 2%, 36% and 48% in female adolescents. The mean number of CAD risk factors was 1.56±0.96. Approximately, 86% of the subjects had at least one type of CAD risk factor when the CAD familial history was considered. Conclusions: Regarding the CAD risk factors analyzed, the adolescent populations studied presented with a similar pattern described in other populations with the same age group, except for blood pressure. Although this population is young (below 18 years old) and resident in Veranópolis County which is considered a high longevity Brazilian region, we detected a high CAD risk factor prevalence. Further studies analyzing genetic and environmental variables may help to elucidate the results described here. The results from this studies strongly support the idea that the prevention of CAD should be started in early life.